Dyspeptic symptoms in patients with type 1 diabetes: endoscopic findings, Helicobacter pylori infection, and associations with metabolic control, mood disorders and nutritional factors - Mariza Faria (Archives of Endocrinology and Metabolism)
Objectives To evaluate, in a group of patients with long-standing type 1 diabetes (DM1), an association of dyspepsia symptoms with: changes in the gastroduodenal mucosa, infection by Helicobacter pylori, glycemic control, and psychological and nutritional factors. Subjects and methods A total of 32 patient with DM1 were studied (age: 38 ± 9 years; females: 25; diabetes duration: 22 ± 5 years). All patients answered a standardized questionnaire for the evaluation of gastrointestinal symptoms and underwent upper gastrointestinal endoscopy, with gastric biopsies for the evaluation of Helicobacter pylori infection. The presence of anxiety and depression was evaluated by the HAD scale. Nutritional parameters were BMI, arm and waist circumference, skinfold measurement, and body fat percentage. Results Upper endoscopy detected lesions in the gastric mucosa in 34.4% of the patients, with similar frequency in those with (n = 21) and without dyspepsia (n = 11). The patients with dyspepsia complaints showed greater frequency of depression (60% vs. 0%; p = 0.001), higher values for HbA1c (9.6 ± 1.7 vs. 8.2 ± 1.3%; p = 0.01) and lower values for BMI (24.3 ± 4.1 vs. 27.2 ± 2.6 kg/m2; p = 0.02), body fat percentage (26.6 ± 6.2 vs. 30.8 ± 7.7%; p = 0.04), and waist circumference (78.7 ± 8 vs. 85.8 ± 8.1 cm; p = 0.02). No association was found between the symptoms and the presence of Helicobacter pylori. Conclusions Dyspepsia symptoms in patients with long-standing DM1 were associated with glycemic control and depression, and they seem to negatively influence the nutritional status of these patients.